2009
DOI: 10.1210/en.2009-0405
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthetic Androgen Receptor Ligand, S42, Works as a Selective Androgen Receptor Modulator and Possesses Metabolic Effects with Little Impact on the Prostate

Abstract: We identified a novel synthetic steroid, S42, as a promising candidate of selective androgen receptor (AR) modulator. Results of the whole-cell binding assay using COS-7 cells exogenously expressing various steroid receptors indicated that S42 specifically binds to AR and progesterone receptor. When orchiectomized Sprague Dawley rats were administered with S42 for 3 wk, the muscle weight of the levator ani was increased as markedly as that induced by 5alpha-dihydrotestosterone (DHT), but the weight of the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Thus, there has been intense interest in the discovery of SARM, and several AR ligands with SARM-like properties have been reported. [29][30][31][32] YK11 acts as a gene-selective agonist of AR in MDA-MB 453 cells. This type of selective gene induction by AR has been observed when AR is liganded with selective AR modulators (SARMs), 31) a class of drugs that produce cell-specific anabolic effects in tissues such as bone and muscle without causing androgenic effects in other tissues such as those of reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there has been intense interest in the discovery of SARM, and several AR ligands with SARM-like properties have been reported. [29][30][31][32] YK11 acts as a gene-selective agonist of AR in MDA-MB 453 cells. This type of selective gene induction by AR has been observed when AR is liganded with selective AR modulators (SARMs), 31) a class of drugs that produce cell-specific anabolic effects in tissues such as bone and muscle without causing androgenic effects in other tissues such as those of reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…The development of selective androgen receptor-modulating therapies may help mitigate many of these side effects. Preclinical and phase II trials of candidate drugs have demonstrated beneficial effects on insulin sensitivity as well as on muscle mass and strength (Gao et al 2005, Dalton et al 2011, Min et al 2009). …”
Section: Additional Therapeutic Perspectivesmentioning
confidence: 99%
“…Furthermore, administration of S42 to orchiectomized Sprague–Dawley rats for 3 weeks was as effective as DHT in increasing the weight of the levator ani muscle, but did not elevate the prostate weight at any dose, in contrast to the effect of DHT. These results suggest that, while sparing the prostate from potentially harmful effects, S42 had an anabolic action in orchiectomized rats [10] .…”
Section: Introductionmentioning
confidence: 74%
“…In an effort to develop a SARM with beneficial activity in energy homeostasis, we previously screened 119 steroid analogs for the ability to induce uncoupling protein-1 mRNA without increasing prostate-specific antigen promoter activity in the human PC cell line, LNCaP [10] . As a result, we identified a novel SARM, S42, which is a structural analog of testosterone [10] . In LNCaP cells, S42 does not induce AR transactivation, but antagonizes 5α-dihydrotestosterone (DHT)-induced AR activation [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation